Vibration Spectroscopy Potential for Beef and Pork Determination - Syahputra, Muhammad Yudha; Juniawan, Alvin; Suprapto, Suprapto; Kurniawan, Fredy (Institut Teknologi Sepuluh Nopember, 2020)
Meat is one of the most foodstuff consumed. The increasing consumption of meat had led some traders to falsify the identity of meat for gaining profit. The meat adulteration case that often occurs is substituting the beef with pork. This adulteration case is very detrimental to consumers, therefore a method to identify the type of meat sold is very necessary. The vibration spectroscopy method, Fourier Transform Infra Red (FTIR), had been developed to analyze the type of beef and pork. The FTIR measurement was carried out with cut raw meat samples without further preparation. The Data obtained from the measurement are infra-red spectrum from beef and pork from 4000-500 cm-1 wavenumber and then the data was analyzed with Principle Component Analysis (PCA) statiscticall method. Projection result with PCA obtained data reduction that can represent all data generated from measurements shown through the Principle Component 1 and Principle Component 2 regions. Based on those projection, beef and pork profile area can be classified properly.